Single-dose VSV-based vaccine protects cynomolgus macaques from disease after Taï Forest virus infection - Paige Fletcher; Kyle L. O’Donnell; Brianna M. Doratt; Delphine C. Malherbe; Chad S. Clancy; Joseph F. Rhoderick; Friederike Feldmann; Patrick W. Hanley; Thomas G. Ksiazek; Thomas W. Geisbert; Ilhem Messaoudi; Andrea Marzi (Emerging Microbes and Infections)
Taï Forest virus (TAFV) is a lesser-known ebolavirus that causes lethal infections in chimpanzees and is responsible for a single human case. Limited research has been done on this human pathogen; however, with the recent emergence of filoviruses in West Africa, further investigation and countermeasure development against this virus is warranted. We developed a vesicular stomatitis virus (VSV)-based vaccine expressing the TAFV glycoprotein as the viral antigen and assessed it for protective efficacy in nonhuman primates (NHPs). Following a single high-dose vaccination, NHPs developed antigen-specific binding and neutralizing antibodies as well as modest T cell responses. Importantly, all vaccinated NHPs were uniformly protected from disease after lethal TAFV challenge while the naïve control group succumbed to the disease. Histopathologic lesions consistent with filovirus disease were present in control NHPs but were not observed in vaccinated NHPs. Transcriptional analysis of whole blood samples obtained after vaccination and challenge was performed to gain insight into molecular underpinnings conferring protection. Differentially expressed genes (DEG) detected 7 days post-vaccination were enriched to processes associated with innate immunity and antiviral responses. Only a small number of DEG was detected in vaccinated NHPs post-challenge while over 1,000 DEG were detected in control NHPs at end-stage disease which mapped to gene ontology terms indicative of defense responses and inflammation. Taken together, this data demonstrates the effective single-dose protection of the VSV-TAFV vaccine, and its potential for use in outbreaks.